1996
DOI: 10.7557/2.16.4.1223
|View full text |Cite
|
Sign up to set email alerts
|

Population Ecology of Caribou in British Columbia

Abstract: Abstract:The abundance and geographic range of woodland caribou (Rangifer tarandus caribou) decreased in many areas of British Columbia during the 1900's. Recent studies have found that predation during the summer is the major cause of mortality and current population declines. Increased moose {Alecs alces) populations may be related to past and current caribou declines by sustaining greater numbers of wolves (Canis lupus). Mortality rates were greater in areas where caribou calved in forested habitats, in clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 12 publications
3
54
0
Order By: Relevance
“…Caribou herds for which calving or summer ranges overlap with moose and wolves have higher mortality rates than herds that spatially separate from areas used by wolves and moose (Bergerud & Page, 1987;Seip, 1992a). Females may compromise nutritional gains by using alpine areas where predation risk may be lower (Bergerud et al, 1984;Bergerud & Page, 1987;Bergerud et al, 1990;Gustine et al, 2006a), but survival is higher (Seip & Cichowski, 1996) than in lower-elevation forests. During seasons when nutritional demands for caribou are high (e.g., pregnant or lactating females in spring), caribou may move to areas containing more abundant or highquality forage and increase risk of predation (Gustine et al, 2006a).…”
Section: Seasonal Habitat Selectionmentioning
confidence: 99%
“…Caribou herds for which calving or summer ranges overlap with moose and wolves have higher mortality rates than herds that spatially separate from areas used by wolves and moose (Bergerud & Page, 1987;Seip, 1992a). Females may compromise nutritional gains by using alpine areas where predation risk may be lower (Bergerud et al, 1984;Bergerud & Page, 1987;Bergerud et al, 1990;Gustine et al, 2006a), but survival is higher (Seip & Cichowski, 1996) than in lower-elevation forests. During seasons when nutritional demands for caribou are high (e.g., pregnant or lactating females in spring), caribou may move to areas containing more abundant or highquality forage and increase risk of predation (Gustine et al, 2006a).…”
Section: Seasonal Habitat Selectionmentioning
confidence: 99%
“…Negative effects can eventually occur, for example, if corridors increase caribou concentration and consequently favour predation (Seip and Cichowski 1996). Despite these possible negative effects, at this stage it seems advisable to maintain corridors, but future research will be needed to determine their effectiveness.…”
Section: G3 Maintain Habitat Connectivitymentioning
confidence: 99%
“…McLellan et al (2006) hypothesized that rapid declines in alternative prey abundance due to severe winters may have resulted in increased searching time by predators and thus greater encounter and kill rates of caribou until predator numbers declined or other ungulates increased. Although this hypothesis remains untested, they suggested that instability of the predator/prey system is why caribou trends often show rapid declines followed by a period of apparent stability (Seip & Cichowski, 1996;McLellan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%